Sequential TPF chemotherapy followed by concurrent chemoradiotherapy in locally advanced head and neck cancer – a retrospective analysis of toxicity and outcomes. Issue 1 (February 2014) - Sanders, IW; Haslett, K; Correa, P; Paterson, C; James, A; Rizwanullah, M; Grose, D
Background and aims: Phase III trials have shown that the addition of a taxane to cisplatin/5FU-based induction chemotherapy (TPF) improves response rates and overall survival in unresectable stage III/IV head and neck cancer. We sought to assess the tolerability, compliance and clinical outcomes of this treatment regime. Methods: A retrospective study of patients treated within a single centre between September 2007 and November 2010. Toxicities were graded according to CTCAE version 3.0. Survival, distant metastasis and local control rates are expressed as percentages at two years using the Kaplan–Meier method. Results: A total of 100 patients were identified (11% stage III, 86% stage IV) and 32% of patients were admitted as an emergency after TPF. The rate of neutropenic fever was 31%, this number fell to 9% when prophylactic G-CSF was used. In addition, 89% of patients underwent radical chemoradiation. Of these, 96% completed the full radiotherapy course. However, only 64% of patients received a minimum of two cycles of concurrent platinum chemotherapy. The two-year overall survival, metastasis free survival and local control rates were 62.6%, 88.5% and 73.3%, respectively. Conclusions: TPF chemotherapy can be delivered safely in a non-trial cohort of patients. There is, however, a significant reduction in concurrent chemotherapy dose intensity. The long-term impact of this remains unclear.